Procedural agreement: general concept and forms (Journal of actual problems of jurisprudence, 2018)
In this article, the authors examined the issues of the new institution of the criminal process as a procedural agreement, namely its concept and procedural form. The institute of procedural agreement shows the development of criminal procedural legislation in a democratic direction, which in its way are aimed at the effectiveness and economy of the criminal procedural legislation.In this article, the authors, having investigated the world and domestic opinions concerning procedural despondency, try to give their own, author’s opinion of the concept of procedural agreement. Also, the authors examined and disclosed the types of procedural agreement, the specifics of their application and the form of the procedural agreement. In accordance with Article 612 of the Criminal Procedure Code of the Republic of Kazakhstan, it ispossible to conclude two types of procedural agreements: in the form of a plea bargain – for crimes ofsmall, medium gravity or grave crimes – in the case of the consent of the suspect accused of suspicionand prosecution; in the form of an agreement on cooperation – for all categories of crimes in facilitatingthe disclosure and investigation of crimes committed by a criminal group, especially serious crimes committedby other persons, as well as extremist and terrorist crimes.The purpose of this article is to explore the procedural agreement based on theoretical and practicalknowledge already accumulated in this field, as well as the norms of the current CCP, on the basisof which to develop proposals for improving the criminal procedural legislation and law enforcementpractice.The relevance of the research topic is conditioned by the fact that in the criminal process the main isto ensure the right to defend the suspect, accused and defendant, as well as ensuring the efficiency andeconomy of the criminal process.On the basis of analysis, the author analyzes the concept and form of the procedural agreement, andalso conducts an analysis of domestic and international practice.Key words: procedural agreement, accused, guilt, criminal trial, prosecutor.